The development impact of seasonal worker schemes: a comparison of European and Pacific experiences. (2nd January 2017) - Brickenstein, Christine
Abstract : Temporary migration regimes have become increasingly popular in recent years and seasonal worker regulations have been advocated for having the potential to influence the development impact in the countries of origin. However, the exact parameters influencing the relationship between seasonal migration and development often remain unclear. This article conducts a comparative analysis of seasonal worker regulations across four countries by examining agricultural seasonal worker regulations in similar settings (France compared to Germany, and Australia compared to New Zealand) as well as in different settings (France and Germany compared to Australia and New Zealand). The result of this comparison suggests that the development impact is mostly influenced by the selection of new and returning workers, the amount of average earrings, the utilisation of workers' income, the form and frequency of remittances, and whether skill acquisition takes place.